# Solve each equation by completing the square need help please

QUESTION POSTED AT 29/05/2020 - 01:23 AM

QUESTION POSTED AT 29/05/2020 - 01:23 AM

Okay, first let's complete the square.

x^2 - 6x + 2 = 0

First, get the +2 to the other side of the equal sign by subtracting 2 from both sides.

x^2 - 6x + 2 = 0

-2 -2

x^2 - 6x = -2.

Now we have to turn our first binomial (x^2 - 6x) into a perfect square trinomial. To do this, we simply divide the second term's coefficient by 2, and then square the result.

-6 / 2 = -3, -3^2 = 9.

We just add this to both sides of the equation.

x^2 - 6x = -2

x^2 - 6x + 9 = -2 + 9

x^2 - 6x + 9 = 7

Now, we need to factor our first trinomial.

Because our trinomial is a perfect square trinomial, we can put it in the form (a + b)^2. To do this, we just take the square root of the first term and the square root of the last term.

√x^2 = x, √9 = 3.

So, x^2 - 6x + 9 factored is (x + 3)^2.

Now we have (x + 3)^2 = 7, and we have finished completing the square.

Now we need to solve for the x intercepts.

Take the square root of both sides of the equal sign, so

√(x + 3)^2 = +/- √7

x + 3 = +/- √7. √7 rounded to the nearest tenth is 2.6.

x + 3 = +/- 2.6, subtract 3 from both sides.

-3 -3

x = +/- 2.6 - 3

x = 2.6 - 3 = -0.4

x = -2.6 - 3 = -5.6

So our x intercepts our approximately -0.4 and -5.6.

Hope this helps!!

Let me know if there's anything you don't understand and I'll try to explain as best I can.

x^2 - 6x + 2 = 0

First, get the +2 to the other side of the equal sign by subtracting 2 from both sides.

x^2 - 6x + 2 = 0

-2 -2

x^2 - 6x = -2.

Now we have to turn our first binomial (x^2 - 6x) into a perfect square trinomial. To do this, we simply divide the second term's coefficient by 2, and then square the result.

-6 / 2 = -3, -3^2 = 9.

We just add this to both sides of the equation.

x^2 - 6x = -2

x^2 - 6x + 9 = -2 + 9

x^2 - 6x + 9 = 7

Now, we need to factor our first trinomial.

Because our trinomial is a perfect square trinomial, we can put it in the form (a + b)^2. To do this, we just take the square root of the first term and the square root of the last term.

√x^2 = x, √9 = 3.

So, x^2 - 6x + 9 factored is (x + 3)^2.

Now we have (x + 3)^2 = 7, and we have finished completing the square.

Now we need to solve for the x intercepts.

Take the square root of both sides of the equal sign, so

√(x + 3)^2 = +/- √7

x + 3 = +/- √7. √7 rounded to the nearest tenth is 2.6.

x + 3 = +/- 2.6, subtract 3 from both sides.

-3 -3

x = +/- 2.6 - 3

x = 2.6 - 3 = -0.4

x = -2.6 - 3 = -5.6

So our x intercepts our approximately -0.4 and -5.6.

Hope this helps!!

Let me know if there's anything you don't understand and I'll try to explain as best I can.

QUESTION POSTED AT 02/06/2020 - 02:02 AM

QUESTION POSTED AT 02/06/2020 - 01:57 AM

QUESTION POSTED AT 02/06/2020 - 01:54 AM

QUESTION POSTED AT 02/06/2020 - 01:53 AM

QUESTION POSTED AT 02/06/2020 - 01:53 AM

QUESTION POSTED AT 02/06/2020 - 01:43 AM

QUESTION POSTED AT 02/06/2020 - 01:43 AM

QUESTION POSTED AT 02/06/2020 - 01:36 AM

QUESTION POSTED AT 02/06/2020 - 01:33 AM

QUESTION POSTED AT 02/06/2020 - 01:32 AM

QUESTION POSTED AT 02/06/2020 - 01:31 AM

QUESTION POSTED AT 02/06/2020 - 01:23 AM

QUESTION POSTED AT 02/06/2020 - 01:21 AM

QUESTION POSTED AT 02/06/2020 - 01:13 AM

QUESTION POSTED AT 01/06/2020 - 05:09 PM

QUESTION POSTED AT 01/06/2020 - 05:03 PM

QUESTION POSTED AT 01/06/2020 - 04:55 PM

QUESTION POSTED AT 01/06/2020 - 04:47 PM

QUESTION POSTED AT 01/06/2020 - 04:47 PM

QUESTION POSTED AT 01/06/2020 - 04:46 PM

QUESTION POSTED AT 01/06/2020 - 04:46 PM

QUESTION POSTED AT 01/06/2020 - 04:45 PM

QUESTION POSTED AT 01/06/2020 - 04:44 PM

QUESTION POSTED AT 01/06/2020 - 04:44 PM

QUESTION POSTED AT 01/06/2020 - 04:44 PM